2015
DOI: 10.18632/oncotarget.6710
|View full text |Cite
|
Sign up to set email alerts
|

p130Cas scaffold protein regulates ErbB2 stability by altering breast cancer cell sensitivity to autophagy

Abstract: Overexpression of the ErbB2/HER2 receptor tyrosine kinase occurs in up to 20% of human breast cancers and correlates with aggressive disease. Several efficacious targeted therapies, including antibodies and kinase inhibitors, have been developed but the occurring of resistance to these agents is often observed. New therapeutic agents targeting the endocytic recycling and intracellular trafficking of membrane in tumor cells overexpressing ErbB2 are actually in clinical development. Nevertheless the mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The mechanism through which p130Cas mediates resistance to Trastuzumab might rely on the increased ErbB2 stability to the cell membrane. This increased stabilization of ErbB2 by p130Cas might be the crucial event driving breast cancer progression and resistance, strengthening the relevance of p130Cas as putative therapeutic target to overcome resistance to Trastuzumab 5 .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The mechanism through which p130Cas mediates resistance to Trastuzumab might rely on the increased ErbB2 stability to the cell membrane. This increased stabilization of ErbB2 by p130Cas might be the crucial event driving breast cancer progression and resistance, strengthening the relevance of p130Cas as putative therapeutic target to overcome resistance to Trastuzumab 5 .…”
Section: Introductionmentioning
confidence: 82%
“…Among them, Trastuzumab was approved for the treatment of breast cancers overexpressing ErbB2, alone or in combination with standard chemotherapy. The mechanism of action of Trastuzumab is complex and not well understood, resulting in modest downregulation of the ErbB2 receptor 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has been shown that Hsp90 inhibition can induce ErbB2 ubiquitination followed by its downregulation [52], however the mechanisms underlying ErbB2 downregulation are still obscure. Recently it has been demonstrated that molecular association between p130Cas and ErbB2 protects the receptor from degradation through autophagy [53]. On this regard, increasing evidence points out that ubiquitination is an important mechanism driving autophagic degradation.…”
Section: Mechanisms Of Erbb2-breast Cancer Therapy Resistancementioning
confidence: 99%
“…On this regard, increasing evidence points out that ubiquitination is an important mechanism driving autophagic degradation. Interestingly, in breast cancer cells overexpressing ErbB2, p130Cas protects ErbB2 from autophagy-mediated degradation by interfering with its ubiquitination, thus suggesting that high levels of p130Cas expression might be crucial to promote resistance to trastuzumab treatment by protecting ErbB2 from degradation [53].…”
Section: Mechanisms Of Erbb2-breast Cancer Therapy Resistancementioning
confidence: 99%